Perception De L Effet Du Conflit Travail-Famille Et Implication Organisationnelle Au Sein Des PME (Global Journal of Science Frontier Research, 2021)
The purpose of this study is to understand how the work-family conflict contributes to the lack of involvement of employees in Cameroonian SMEs and the means to be implemented to allow a good involvement of employees in this category of companies in Cameroon We conducted exploratory qualitative research with a sample of employees working in Cameroonian SMEs The results of our analyses have thus led to the conclusion that the work-family conflict contributes to the lack of involvement of employees within companies SMEs That is to say the difficulty of reconciling the two spheres family and work by employees influences the normative calculated and affective involvement in work
Keywords: work-family conflict; normative involvement; emotional involvement; calculated involvement; and organizational involvement